Immigration and US shelter prices: The role of geographical and immigrant heterogeneity - James Cabral; Walter Steingress (Bank of Canada, 2024)
The arrival of immigrants increases demand for housing and puts upward pressure on shelter prices. Using instrumental variables based on the ancestry composition of residents in US counties, we estimate the causal impact of immigration on local shelter prices. We show that the impact of immigrants is heterogeneous across locations. The increase in shelter prices is greater in counties where immigrants have higher levels of education and in counties that issue fewer building permits. We also find that the house prices respond more to immigration than rent prices do. The larger issuance of building permits for multi-unit homes than for single-unit homes can reconcile the different price reactions. Based on empirical estimates, we find that the predicted contribution of immigration to US shelter price growth is small, around 2%, because the arrival of immigrants accounts for a small share in local population changes. When we apply our estimates to population movements across counties within the United States, our model can predict 50% to 60% of observed shelter price growth over the past 30 years.
Keywords: J61; R23; R31; 330; Housing; Inflation and prices; International topics; Regional economic developments